HANDWRITING LEGIBILITY AS CRITERION FOR BURNOUT - Petrov, Petr; Averyanov, Sergey; Iskhakov, Ilgiz; Nurimanov, Rustam; Bikmukhametova, Guzel (Revista Inclusiones, 2020)
The article deals with the relationship between the legibility of dentists’ handwriting and their gender, workload, length of service, burnout and pen ergonomics. 178 dentists and 315 students of the Bashkir State Medical University took part in the study. It has been proven that there is a direct correlation between the aforementioned factors.